Stakeholders’ Experiences of Research Integrity Support in Universities: A Qualitative Study in Three European Countries. - Evans, Natalie; Buljan, Ivan; Valenti, Emanuele; Bouter, Lex; Marušić, Ana; de Vries, Raymond; Widdershoven, Guy (Science & Engineering Ethics, 2022)
Fostering research integrity (RI) increasingly focuses on normative guidance and supportive measures within institutions. To be successful, the implementation of support should be informed by stakeholders’ experiences of RI support. This study aims to explore experiences of RI support in Dutch, Spanish and Croatian universities. In total, 59 stakeholders (Netherlands n = 25, Spain n = 17, Croatia n = 17) participated in 16 focus groups in three European countries. Global themes on RI support experiences were identified by thematic analysis. Themes identified were: ‘RI governance and institutional implementation’, ‘RI roles and structures’, ‘RI education and supervision’, and ‘Infrastructure, technology and tools supporting daily practice’. Experiences of support differed between countries in relation to: the efforts to translate norms into practice; the extent to which RI oversight was a responsibility of RE structures, or separate RI structures; and the availability of support close to research practice, such as training, responsible supervision, and adequate tools and infrastructure. The study reinforces the importance of a whole institutional approach to RI, embedded within local jurisdictions, rules, and practices. A whole institutional approach puts the emphasis of responsibility on institutions rather than individual researchers. When such an approach is lacking, some stakeholders look for intervention by authorities, such as funders, outside of the university.